2012
DOI: 10.5812/hepatmon.6141
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Hepatitis C Virus Core Antigen in Immunized Balb/C Mice

Abstract: Background Hepatitis infection represents one of the important causes of morbidity and mortality in developing countries, however there is not any effective vaccine against hepatitis C which is one of the significant problems in vaccine project. Objectives The aim of the present study is to evaluate the role of HCV core protein in inducing IFN-Gamma secretion and TCL activities as a vaccine in Balb/C mice. Material and Methods Our previous cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One of the major problems in development of HCV vaccine is its wide genetic variants. It has been shown that core antigen is a highly conserved protein (2). Serum antibodies against HCV core protein epitopes (residues 7-21, 31-45, 49-63, 99-113) were shown in HCV patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major problems in development of HCV vaccine is its wide genetic variants. It has been shown that core antigen is a highly conserved protein (2). Serum antibodies against HCV core protein epitopes (residues 7-21, 31-45, 49-63, 99-113) were shown in HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to contribution of all amino acid residues of HCV core, total of 191 amino acids of this protein were included in vaccine design. Indeed, the conservative feature of the core gene in different HCV genotypes and the low susceptible of mutation in this region, make this protein an ideal candidate for HCV vaccine (2). Therefore, the production of core protein was done in different expression systems (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…HCV core antigen is a highly conserved protein and a major target to develope HCV preventive vaccines [19]. The generation of the core protein has been attempted in various expression systems [9,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%